Physical and mechanical properties of soya bean seeds in relation to the design of oil extractors - Bako, Tanko; Mamai, Ezekiel Ambo; Bature, Boman James (Journal of Postharvest Technology, 2019)
Physical and mechanical properties are very important in the design and manufacturing of processing machines. In this research work, the physical and mechanical properties of soya bean seeds were determined as design parameters for the development of an oil expeller for the crop. The physical properties determined were length, width, thickness, arithmetic mean diameter, geometric mean diameter, roundness, sphericity, aspect ratio, surface area, projected area, volume, moisture content, one thousand seed weight, bulk density, true density and porosity. The average seed length, width and thickness were found to be 6.67 ± 0.27, 5.60 ± 0.22 and 4.64 ± 0.24 mm respectively. The average arithmetic and geometric mean diameters were 5.64±0.19 and 5.58±0.17 mm respectively. The average roundness, sphericity and aspect ratio were 0.7879±0.023, 0.8359±0.021 and 0.8396±0.025 respectively. The mean surface area, projected area and volume were 97.66±32.58 mm2, 29.34±3.47 mm2 and 90.75±29.64 mm3respectively. The average moisture content was 7.34±0.32% dry basis and the thousand kernel weight was 104.88±0.53 g. The average bulk and true densities were 750.00 ± 3.28 and 1250.00 ± 4.45 kgm-3respectively and the porosity was 40.02 ±0.061%. The mechanical properties determined in this study were angle of repose, coefficient of static friction, shear strength and compressive strength. The mean angle of repose was 27.00±0.37o while the mean coefficient of static friction on mild steel surface was 0.52±0.022. The mean shear strength and compressive strength of the seeds were 284.56±25.13 and 657.33±46.62 N/mm2 respectively. These parameters would provide important and essential data for the efficient design of oil extractors.